Identification of Pathogenic Mutations and Investigation of the NOTCH Pathway Activation in Kartagener Syndrome - Yue, Yongjian; Huang, Qijun; Zhu, Peng; Zhao, Pan; Tan, Xinjuan; Liu, Shengguo; Li, Shulin; Han, Xuemei; Cheng, Linling; Li, Bo; Fu, Yingyun (Frontiers in Genetics, 2019)
Primary ciliary dyskinesia (PCD), a rare genetic disorder, is mostly caused by defects in more than 40 known cilia structure-related genes. However, in approximately 20–35% of patients, it is caused by unknown genetic factors, and the inherited pathogenic factors are difficult to confirm. Kartagener syndrome (KTS) is a subtype of PCD associated with situs inversus, presenting more complex genetic heterogeneity. The aim of this study was to identify pathogenic mutations of candidate genes in Chinese patients with KTS and investigate the activation of the heterotaxy-related NOTCH pathway. Whole exome sequencing was conducted in five patients with KTS. Pathogenic variants were identified using bioinformatics analysis. Candidate variants were validated by Sanger sequencing. The expression of the NOTCH pathway target genes was detected in patients with KTS. We identified 10 KTS-associated variants in six causative genes, namely, CCDC40, DNAH1, DNAH5, DNAH11, DNAI1, and LRRC6. Only one homozygote mutation was identified in LRRC6 (c.64dupT). Compound heterozygous mutations were found in DNAH1 and DNAH5. Six novel mutations were identified in four genes. Further analyses showed that the NOTCH pathway might be activated in patients with KTS. Overall, our study showed that compound heterozygous mutations widely exist in Chinese KTS patients. Our results demonstrated that the activation of the NOTCH pathway might play a role in the situs inversus pathogenicity of KTS. These findings highlight that Kartagener syndrome might be a complex genetic heterogeneous disorder mediated by heterozygous mutations in multiple PCD- or cilia-related genes.